IMMUNO-INFLAMMATORY MARKERS ASSOCIATED WITH LEFT VENTRICULAR REMODELING IN ISCHEMIC HEART DISEASE - Ganieva Shaxzoda Shavkatovna; Negboyev Zokirjon Furqat o’g’li (Modern American Journals, 2025)
The article explores endothelial damage factors in arterial hypertension and ischemic heart disease, forming a cardiovascular syntropy. The cytokines considered as markers of endothelial dysfunction include IGF-I, VEGF, TGF-β1, and serum procalcitonin. The study found that patients with elevated VEGF levels have a high risk of developing and progressing cardiovascular pathology—particularly myocardial fibrosis and hypertrophy—against the background of arterial hypertension, regardless of its severity.
Keywords: Cardiovascular diseases, ischemic heart disease, arterial hypertension, cytokines, immunological markers